Selection of the effective dwelling house walls by applying attributes values determined at intervals - Zavadskas, Edmundas Kazimieras; Kaklauskas, Artūras; Turskis, Zenonas; Tamošaitienė, Jolanta (Journal of Civil Engineering and Management, 2008)
The higher life quality standards, the changes of habits and new well‐being requirements have led to an increase in the demand for housing. Decision‐making problems in construction management often involve a complex decision‐making process in which multiple requirements and conditions have to be taken into consideration simultaneously. However, not every attribute used in multidimensional scaling is equally and precisely weighted in the real world. Thus quantitative and qualitative assessments are often required to deal with uncertainty, subjective and imprecise data. The accuracy of performance measures in common multi‐attribute methods is usually assumed to be accurate. Grey theory is a new technique for performing prediction, relational analysis and decision‐making in many areas. This paper considers the application of grey relations methodology for defining the utility of an alternative and is proposed as a method of multiple criteria COmplex PRoportional Assessment of alternatives with Grey relations (COPRAS‐G). In this model parameters of the alternatives are determined by the grey relational grade and are expressed in intervals. A case study of assessing external walls of four alternatives was used to demonstrate the applicability and the effectiveness of the proposed approach. The results show that this method can be implemented as an effective decision aid in multi‐attribute selection. Daugiabučių namų išorinių sienų efektyvumo vertinimas, kai efektyvumo rodiklių reikšmės aprašomos intervalais Santrauka. Straipsnio tikslas – pasiūlyti alternatyvią daugelio rodiklių vertinimo metodiką. Šios metodikos išskirtinumas – rodiklių reikšmės, aprašomos intervalais. Tai labiau atitinka realias aplinkos sąlygas ir galimas reikšmes. Modelis su intervaluose pateiktomis efektyvumo rodiklių reikšmėmis pritaikytas E. K. Zavadsko ir A. Kaklausko sukurtam metodui COPRAS (Complex Proportional Evaluation). Taip gautas naujas metodas COPRAS-G. Šis metodas pritaikytas daugiabučių namų išorinių sienų efektyvumo vertinimo uždaviniui spręsti. Sudaryta efektyvumo rodiklių sistema, nustatyta efektyvumo rodiklių reikšmė, rodiklių rangas. Pagal sudarytą modelį pritaikę COPRAS-G metodą, galime spręsti daugelį statybos, vadybos alternatyvų vertinimo uždavinių. Reikšminiai žodžiai: sienos, alternatyvos, daugiatikslis parinkimas, vertinimas, COPRAS, COPRAS-G, pilkieji skaičiai. First Published Online: 14 Oct 2010